The responses of Spinifex littoreus to sand burial on the coastal area of Pingtan Island, Fujian Province, South China. Issue 2 (3rd April 2021) - Song, Shuang; Du, Jianhui; Wu, Qirui; Ni, Mingyang; Wang, Yijia; Zhang, Yingling
ABSTRACT: The adaptive capacity of psammophytes to sand burial is crucial for the ecological restoration of coastal dune systems. The responses of Spinifex littoreus to diﬀerent sand burial depths and levels were examined on the coast of Pingtan Island, Fujian Province, South China. The results indicated that, compared with the control group (CG), sand burial on the S. littoreus stolons had no signiﬁcant impact on the vertical growth of its conjoint ramets. However, the horizontal growth of S. littoreus stolons was stimulated and signiﬁcantly increased in half-intense (HI) and complete-intense (CI) sand burial treatments by 24.56% and 40.79%, respectively. Throughout the experiment, about 96% of adventitious roots were observed on the base section of stolons, while no roots in the control group (CG). After 20-day artiﬁcial sand burial treatments, the dry weight ratio between stem and leaf of S. littoreus was decreased in all three sections of stolons, especially for the top sections. Overall, S. littoreus can adapt to the complete and intense sand burial in growing season by rapid growth of stolons, abundant production of adventitious roots on the stolon base, and more germination of leaves on the stolon top.